2022
DOI: 10.36312/ijece.v1i1.728
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing Prospective STEM Teachers' Critical Thinking Skill through Virtual Simulation-Assisted Remote Inquiry in Fourier Transform Courses

Abstract: Alignment of inquiry learning has embarked on remote inquiry as a replacement for face-to-face inquiry. On the other hand, the current technological developments bring opportunities to use it as a learning resource to support critical thinking. The current study explores the impact of virtual simulation-assisted remote inquiry in Fourier transform courses on prospective STEM teachers' (PST) critical thinking (CT) skills. The experimental design employed a randomized pretest-posttest control group was employed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
4
17
0
Order By: Relevance
“…The supporting design or innovative learning design process is the key to success in achieving learning goals in the 21st century (Prayogi & Verawati, 2020). It has been proven in many studies that innovative learning models or methods oriented towards problem-solving, inquiry, and exploration can train and improve students' thinking performance in the 21st century (Bilad et al, 2022;Prayogi et al, 2018aPrayogi et al, , 2018bPrayogi & Asy'ari, 2013;Verawati et al, 2020Verawati et al, , 2021. Learning ways that lead each individual in their learning process towards strengthening thinking is a form of aggressiveness in the 21st-century education dimension, and this is a must considering the role of deep-thinking ways that learners need to be able to compete in today's world and future.…”
Section: Introductionmentioning
confidence: 99%
“…The supporting design or innovative learning design process is the key to success in achieving learning goals in the 21st century (Prayogi & Verawati, 2020). It has been proven in many studies that innovative learning models or methods oriented towards problem-solving, inquiry, and exploration can train and improve students' thinking performance in the 21st century (Bilad et al, 2022;Prayogi et al, 2018aPrayogi et al, , 2018bPrayogi & Asy'ari, 2013;Verawati et al, 2020Verawati et al, , 2021. Learning ways that lead each individual in their learning process towards strengthening thinking is a form of aggressiveness in the 21st-century education dimension, and this is a must considering the role of deep-thinking ways that learners need to be able to compete in today's world and future.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, competent human resources are needed to apply existing technology in e-learning systems [33]. Well-designed e-learning supported by other adequate technologies can serve as a digital pedagogy to enhance strong ways of thinking [34], and in the end it can improve better learning outcomes [35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The selection of appropriate learning materials can also help to train students' creativity and encourage students to be more active in their learning (Bilad et al, 2022). Based on the research of (Hidayat et al, 2021) showed that impulse and linear momentum electronic teaching materials are feasible to use in learning and can improve scientific literacy.…”
Section: Introductionmentioning
confidence: 99%